Jornada laboral: importancia y aspectos críticos de su regulación - Ávalos Rodríguez, Brian (2019)
The present article analyzes the benefits of the limitations on the working day and the reasons why this measure benefits workers, the State and society as a whole. The author refers to the regulation in the Peruvian legal system and presents proposals that allow greater flexibility for workers, in order for the workers to fully develop.